The Relationship Between Knowledge Level and Adolescent Girls’ Behavior Regarding Personal Hygiene During Menstruation in Tobelo District - Olivia Asih Blandina; Yulina Mahaling (BIOSAINSTEK, 2026)
This study aims to determine the relationship between the level of knowledge and the behavior of young women regarding personal hygiene during menstruation in Tobelo District. The research method used in this research is descriptive analytic quantitative research with a crosssectional approach with a total population of 4,688 young women in Tobelo District, a total sample of 370 respondents. The sampling technique was carried out using simple random sampling. Data were collected using questionnaires and analyzed univariately and bivariately using Spearman's rho analysis. The results showed that the knowledge level of young women was not good at 74%, good at 26% and personal hygiene behavior during menstruation was not good at 55%, good at 45% and there was a relationship between knowledge and behavior of young women about personal hygiene during menstruation at Tobelo District (P=0.00). Based on the results of the study, it can be concluded that the level of knowledge of young women about menstruation is included in the unfavorable category of 74% so that the behavior of young women regarding personal hygiene during menstruation is in the unfavorable category of 55%, where good knowledge is very important in behaving so there is a relationship between knowledge with the behavior of young women regarding personal hygiene during menstruation in Tobelo District.